Exaggerated interventricular dependence among patients with pectus excavatum: Combined assessment with cardiac MRI and Chest CT - Deviggiano, Alejandro (2017)
OBJECTIVE. We sought to explore whether patients with pectus excavatum have exaggerated interventricular dependence and to evaluate the impact of the malformation severity (assessed on CT) on both anatomic and functional cardiac parameters (assessed on cardiac MRI). SUBJECTS AND METHODS. The current study involved consecutive patients with a diagnosis of pectus excavatum who were referred to undergo cardiac MRI and chest CT to establish surgical candidacy or to define treatment strategies. RESULTS. Sixty-two patients with pectus excavatum underwent cardiac MRI and chest CT. Fifty (81%) patients were male, and the median age was 17.5 years (range, 14.0-23.0 years). Forty-seven (76%) patients had evidence of right ventricular compression. The left ventricle showed a significantly decreased end-diastolic volume (inspiration vs expiration: 70.4 ± 11.6 vs 76.1 ± 13.7 mL/m2, respectively; p = 0.01) and a significantly higher eccentricity index (1.52 ± 0.2 vs 1.20 ± 0.1, p < 0.0001) during inspiration than during expiration. The median respiratory-related septal excursion was 8.1% (interquartile range, 5.1-11.7%). Patients with pericardial effusion showed a significantly higher pectus excavatum severity index than patients without pericardial effusion (6.3 ± 3.4 vs 4.4 ± 1.3, respectively; p = 0.003). Patients with a relative septal excursion equal to or larger than 11.8% showed a significantly higher pectus excavatum severity index than patients with a relative septal excursion of less than 11.8% (6.3 ± 2.6 vs 4.7 ± 2.4, respectively; p = 0.05). CONCLUSION. In this study, patients with pectus excavatum showed significant alterations of cardiac morphology and function that were related to the deformation severity and that manifest as an exaggerated interventricular dependence.